METHODS OF ENSURING ECONOMIC SECURITY IN THE BANKING SECTOR (International Conference on Economics, Finance, Banking and Management, 2025)
Ensuring economic security in the banking sector is one of the most important tasks for maintaining financial stability and the successful operation of banks. This paper examines the key methods and approaches aimed at minimizing risks and threats faced by banks, including risk management, maintaining capital and liquidity, internal control, cybersecurity, investment diversification, and compliance with regulatory requirements. The emphasis is placed on the importance of strategic forecasting and crisis management, as well as the need for continuous improvement of security systems to ensure the resilience of banks in conditions of economic instability.